Gallium-niobium nanofiber surface of niobium/PEKK composite with anti-inflammatory, osteogenesis and anti-bacterial effects for facilitating osteoblastic differentiation and ameliorating osteointegration. (1st January 2023) - Wei, Wu; Yang, Ruixia; Yu, Quan; Zhao, Jun; Li, Weizhou
Abstract: Biomaterial-induced infection and inadequate osteointegration are regarded as two major reasons for the failure of implants. Herein, niobium (Nb)/polyetherketoneketone (PEKK) composite (NPC) was prepared, and a gallium (Ga)-Nb nanofiber surface on NPC (NPCG) was fabricated through sequential treatment with sodium hydroxide and gallium nitrate solution. Compared with PEKK and NPC, NPCG with nanofiber surface exhibited significant enhancements in surface properties with higher hydrophilicity and roughness, etc. NPCG remarkably facilitated multiplication and osteoblastic differentiation of bone mesenchymal stem cells in vitro . Moreover, NPCG obviously promoted the RAW264.7 cells polarization to M2 macrophages, which secreted anti-inflammatory cytokines in vitro, demonstrating an anti-inflammatory effect. Furthermore, NPCG significantly boosted osteogenesis and ameliorated osseointegration in vivo . The enhancements of osteoblastic response and M2 macrophage polarization in vitro and osseointegration in vivo for NPCG were attributed to the Ga–Nb nanofiber surface. Further, NPCG displayed outstanding bactericidal capability, which not only inhibited the bacteria growth in vitro but also resisted infection in vivo owing to the sustained release of Ga ions from the nanofiber surface. In short, NPCG with good biocompatibility exhibited anti-inflammatory, bactericidal and osteogenic capabilities, which facilitated osteoblastic differentiation and M2 macrophage polarization, and ameliorated osseointegration, thereby revealing great potential for bone substitute in orthopedics. Graphical abstract: Fabrication of Ga–Nb nanofiber surface of niobium/PEKK composite with anti-inflammatory, osteogenesis and anti-bacterial effects for facilitating osteoblastic differentiation and ameliorating osteointegration as well as preventing infection. Image 1